2017
DOI: 10.1016/j.scijus.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Design, optimisation and preliminary validation of a human specific loop-mediated amplification assay for the rapid detection of human DNA at forensic crime scenes

Abstract: The identification of samples at a crime scene which require forensic DNA typing has been the focus of recent research interest. We propose a simple, but sensitive analysis system which can be deployed at a crime scene to identify crime scene stains as human or non-human. The proposed system uses the isothermal amplification of DNA in a rapid assay format, which returns results in as little as 30min from sampling. The assay system runs on the Genie II device, a proven in-field detection system which could be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
1
4
1
Order By: Relevance
“…2 ), but it did slightly decrease the amplicon signal in a concentration-dependent manner. Complete inhibition of the reaction was observed at 25 µM, which is on the same order of magnitude as the concentration that causes complete inhibition of qPCR (80 µM) 36 and is consistent with a previous report 17 for LAMP (> 20 µM). It has been shown before that hematin collisional quenches fluorescence of dyes such as ROX and sequesters magnesium from polymerases inhibiting the polymerase 36 .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…2 ), but it did slightly decrease the amplicon signal in a concentration-dependent manner. Complete inhibition of the reaction was observed at 25 µM, which is on the same order of magnitude as the concentration that causes complete inhibition of qPCR (80 µM) 36 and is consistent with a previous report 17 for LAMP (> 20 µM). It has been shown before that hematin collisional quenches fluorescence of dyes such as ROX and sequesters magnesium from polymerases inhibiting the polymerase 36 .…”
Section: Resultssupporting
confidence: 91%
“…Complete product (not fluorescence) inhibition was observed at 9 µg/mL, which is on a similar order of magnitude to concentrations that inhibit qPCR (1000 ng per 20 µL; 50 µg/mL; reactions supplemented with BSA that helps prevent amplification inhibition) 45 . Notably, we observed LAMP inhibition at lower concentrations than previous reports (inhibition not observed at even 20 µg/mL) 17 . The reasons for this could include that the previous report used a proprietary polymerase and buffer mix for LAMP (Optigene; cat.…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…Analysis shows that participants believe that once introduced, the impact of the field-based intervention would be positive ( Table 3) [19,28,29]. This has often been in due to the high demands in law enforcement to analyse more DNA samples faster at less expense to increase the speed of casework resolution [13,30,31].…”
Section: Perceived Benefits Regarding the Adoption Of Field-based Insmentioning
confidence: 99%
“…Thus, we hypothesized that its rapidity and simplicity make it suitable for screening human and human male DNA. Previous studies have reported the LAMP assays targeting human DNA for forensic use [ 5 – 7 ]. Another study has reported a male DNA-specific LAMP assay that can detect as low as 1 pg of male DNA within 20 min [ 8 ].…”
Section: Introductionmentioning
confidence: 99%